Alternative metallocenes in floating catalyst-CVD: synthesis of novel carbon nanostructures - Lepak-Kuc, Sandra; Lekawa-Raus, Agnieszka; Jakubowska, Malgorzata; Koziol, Krzysztof K. (Dovepress (T&F Group), 2025)
Introduction: The floating catalyst chemical vapour deposition (FC-CVD) method is widely used for synthesising carbon nanotubes (CNTs), typically with ferrocene as the catalyst. This study explores the use of alternative, nonferrous metallocenes to investigate their impact on carbon nanostructure formation. Methods: Six metallocenes - ferrocene, cobaltocene, ruthenocene, vanadocene, manganocene, and magnesocene - were tested under comparable FC-CVD conditions. The resulting materials were characterised using scanning electron microscopy (SEM), Raman spectroscopy, and energy-dispersive X-ray spectroscopy (EDS). Results and Discussion: Ferrocene produced vertically aligned CNT carpets with high crystallinity. Cobaltocene and magnesocene also yielded CNTs, though less aligned and more defective. Ruthenocene and vanadocene resulted in disordered graphitic carbon without nanotube morphology, confirmed by the presence of broad D and G bands in Raman spectra. Notably, manganocene catalysed the formation of dendritic structures with oxidised and functionalised surfaces, exhibiting unique morphologies distinct from conventional CNTs. Conclusion: These results highlight the ability of nonferrous metallocenes to direct the growth of unconventional carbon nanostructures. The findings suggest new possibilities for tailoring nanocarbon morphology through catalyst selection, particularly for applications requiring high surface area or chemical functionality.
Keywords: CVD; metallocene; catalyst; carbon nanotube; carbon nanostructure; 40 Engineering; 34 Chemical Sciences; 4018 Nanotechnology